Efektivitas Pemberian Ekstrak Daun Katuk Terhadap Produksi Asi Dan Peningkatan Berat Badan Bayi Praktik Mandiri Bidan Wilayah Kabupaten Madiun - Febriyanti Dwi Asokawati; Juda Julia Kristiarini; Fatimah Sari (Journal of Health (JoH), 2021)
Breast milk is the best food for the baby's needs from the beginning of life. However, a survey in Indonesia reported that 38% of mothers stopped breastfeeding due to a lack of milk production caused by various factors such as maternal psychology and nutrition. Several types of plants have traditionally been used by nursing mothers to increase breast milk production, one of which is Sauropus androgynus or katuk leaves which contain important nutrients such as protein, vitamin C, vitamin D, calcium, and folic acid without reducing the quality of breast milk. Katuk leaf extract can increase the mother's milk production up to 50.47%. The general objective of this study was to determine the relationship between giving katuk leaves to breast milk production and increasing infant weight at the WiIayah Midwife Independent Practice, Madiun Regency. This research uses Quasi Experiment method with pre-test and post-test design. The sampling technique used purposive sampling and obtained a sample of 60 nursing mothers who will be given a volume measurement instrument, a control card for measuring breast milk volume filled in by postpartum mothers who will monitor their milk production every day. The results showed a decoction of katuk leaves and extracts. Katuk leaf is effective in meeting the adequacy of breast milk and is proven to increase baby's weight. To test the baby's weight gain using a tool using an observation sheet of baby's weight gain before and after the research was conducted. The results of hypothesis testing using the paired t-test showed that there was a relationship between giving katuk leaf extract to increasing breast milk production.